Process for recovering propylene-ethylene copolymers
The propylene-ethylene copolymer is solved by polymerizing propylene and ethylene under unit-point catalyst and extruding into particles after mixing with clarifier in an extruder, the propylene-ethylene copolymer is solved without sacrificing other properties. Problem, achieving balance of properties and the effect of suitable for packaging and injection molding applications.
Patent Information
- Application Number
- CN202180066348.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-30
- Filing Date
- 2021-09-27
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-09-27
AI Technical Summary
The prior art is difficult to improve the mechanical and optical properties of propylene-ethylene copolymers without sacrificing other properties, especially in packaging and injection molding applications.
By polymerizing propylene and ethylene in a continuous polymerization reactor in the presence of a unit point catalyst, the resulting copolymer powder is collected and kneaded with a clarifier in an extruder, and the mixture is subsequently extruded into particles, the process parameters are adjusted to obtain good Photomechanical capability propylene-ethylene copolymer particles.
The properties of propylene-ethylene copolymer are achieved, with good flexural modulus, Chapy notch impact strength and low haze. They are suitable for packaging and injection molding applications, reducing waste and avoiding environmental pollution.
Smart Images

Figure BDA0004148506930000151 
Figure BDA0004148506930000161 
Figure HDA0004148506940000011
Abstract
Description
Technical Field
[0001] The present invention provides a process for recycling propylene-ethylene copolymers to obtain polymers having good optical and mechanical properties and good processability.
[0002] The present invention further relates to the propylene-ethylene copolymers obtained by said process and articles made therefrom. Background Art
[0003] Polypropylene-based copolymers, such as propylene-ethylene copolymers, are widely used in molding applications, such as thin-wall packaging applications, which require a combination of good mechanical properties - such as high stiffness and impact strength - and optical properties.
[0004] Meeting the demands can be challenging because many polymer properties are directly or indirectly related. Often, improving a particular property can only be achieved at the expense of another property. For example, stiffness can be increased by increasing the crystallinity and / or relative amount of homopolymer in the composition. However, due to this modification, the material becomes more brittle, resulting in poorer impact properties and / or poorer optical properties.
[0005] Impact behavior or optical properties can be improved by increasing the comonomer content. As a result, the material will become softer and looser in terms of stiffness. As a result, impact or optical properties (such as haze) appear to be contradictory to stiffness.
[0006] Furthermore, processability is related to the viscosity or flowability of the polymer: especially for thin-walled articles, complex tool designs or fast production cycles, good flowability in the sense of a high MFR is essential. At the same time, it is well known that polymers with a high MFR tend to be more brittle in the sense of low impact strength, especially at low temperatures.
[0007] If the polymerization is carried out in the presence of a single-site catalyst, additional effects must be considered.
[0008] Specifically, the single-site catalysts that are increasingly used for copolymerization of propylene with other comonomers result in highly random insertion of comonomer units along the chain. Highly random comonomer insertion improves optical behavior. The inherently narrow molecular weight distribution (MWD) produced by polymerization using the single-site catalysts further reduces the amount of extractable fractions compared to polymers produced in the presence of traditional Ziegler-Natta catalysts.
[0009] However, the highly random comonomer insertion of single-site based polypropylene may have an adverse effect on the mechanical properties of the final polymer: based on the highly random comonomer distribution, these polypropylene grades tend to have lower stiffness than Ziegler-Natta grades at similar comonomer content, yet provide lower impact behavior. The aforementioned narrow MWD exacerbates the reduction in stiffness. In addition, the main disadvantage of polypropylene random copolymers produced by single-site catalysis is their poor nucleation reaction. This manifests itself in lower crystallization temperatures compared to polymers produced by Ziegler-Natta catalysis with similar polymer properties, such as comonomer content and type, amount of soluble fraction, etc.
[0010] Most propylene (co)polymer production is carried out by large-scale continuous processes. Such processes allow for efficient production. However, when switching from the production of one well-defined polymer product to another, random-specification materials are produced. Typically, these random-specification materials are produced during a transition phase, which is a period when the comonomer content, Mw and MFR of the polymer gradually change due to dynamic process conditions. Therefore, the random-specification materials obtained are usually substandard commodity grades or industrial waste.
[0011] Description of the Prior Art
[0012] WO 2019 / 197384 aims to provide a bimodal polypropylene random copolymer produced in the presence of a single-site catalyst and exhibiting an improved balance of properties, namely nucleation response, crystallization temperature, mechanical and optical properties.
[0013] EP 3 617 238 A1 aims at providing unimodal propylene random copolymers with specific comonomer insertion, in particular specific comonomer distribution (CD) between the chains. These polypropylene materials show a beneficial balance of stiffness, impact resistance, clarity, haze and flow. Summary of the invention
[0014] Purpose of the Invention
[0015] An object of the present invention is to recycle propylene copolymer materials of random specifications to reduce waste and thus avoid environmental pollution. In addition, from an economic point of view, it will be advantageous to recycle such materials.
[0016] It is therefore an object of the present invention to provide a process for recycling propylene copolymer material wherein random specification propylene material is modified to obtain a polypropylene copolymer having a good balance of properties and suitable for packaging and / or injection molding applications.
[0017] More specifically, it is an object of the present invention to provide propylene random copolymers having a low XCS content and good photomechanical ability (OMA).
[0018] In this application, the photomechanical ability (OMA) is understood to be the product of the flexural modulus and the Charpy notched impact strength (NIS), divided by the haze value (Haze 2) of a 2 mm thick injection molded plaque, that is:
[0019] OMA = (flexural modulus [MPa] * NIS [kJ / m2]) / haze 2 [%]. SUMMARY OF THE INVENTION
[0021] Surprisingly, it has been found that the above object can be achieved by the following method. Therefore, the present invention relates to a method for recovering propylene-ethylene copolymer, comprising the following steps:
[0022] a) polymerizing propylene and ethylene in a continuous polymerization reactor under dynamic conditions in the presence of a single-site catalyst,
[0023] b) collecting the obtained propylene-ethylene copolymer powder from step a) to obtain a mixture (M) of propylene-ethylene copolymer powders having an MFR2 (ISO 1133, 230°C, 2.16 kg) in the range of 1.5 to 80.0 g / 10 min, an ethylene content in the range of 1.0 to 50.0 g / 10 min, based on the total weight of the mixture (M).
[0024] 4.0 wt %,
[0025] c) mixing the mixture (M) and a clarifying agent in an extruder in the presence of a free radical initiator, wherein the amount of the clarifying agent is 0.01 to 0.5 based on the total weight of the propylene-ethylene copolymer powder mixture.
[0026] 1.0 wt%, and
[0027] d) extruding the mixture into granules;
[0028] Wherein, in step a), the dynamic conditions are such that the ethylene content and the melt flow rate (MFR2) of the obtained copolymer gradually change from a first predetermined ethylene content E1 to a second predetermined ethylene content E2, and from the first predetermined melt flow rate MFR 2-1 Gradually change to a second predetermined melt flow rate MFR 2-2 ;
[0029] Wherein, when the polymer produced in step a) has a first ethylene content E1 and a melt flow rate MFR 2-1 When the copolymer powder in step b) is collected, and when the polymer produced in step a) has a second ethylene content E2 and a melt flow rate MFR 2-2 When the copolymer powder in step b) is collected, stop collecting; and
[0030] Wherein, the particles obtained in step d) have the following properties:
[0031] i) MFR2 (ISO 1133, 230°C, 2.16kg) in the range of 20 to 120 g / 10min,
[0032] ii) MFR 2颗粒 / MFR 2粉末 The ratio is >1,
[0033] iii) an ethylene content in the range of 1.0 to 4.0 wt. %,
[0034] iv) a crystallization temperature Tc determined by DSC according to ISO 11357-3:1999 in the range of 100 to 125°C, and
[0035] v) a flexural modulus of 850 MPa or more, the flexural modulus being 1000 MPa or more according to ISO 178.
[0036] The test was performed in three-point bending on injection molded samples of 80×10×4 mm prepared by 1873-2.
[0037] Furthermore, the present invention relates to propylene-ethylene copolymer particles obtainable by the above process and exhibiting the desired properties.
[0038] In another aspect, the present invention relates to an article, preferably a cup, comprising, preferably consisting of, particles of a propylene-ethylene copolymer as described above.
[0039] Finally, the present invention also relates to the use of the propylene-ethylene copolymer particles as described above in injection molding applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] FIG. 1 shows the time course of individual process parameters during step b) of the method according to the invention using IB1 as an example.
[0041] FIG. 2 shows the time course of individual process parameters during step b) of the method according to the invention using IB2 as an example. DETAILED DESCRIPTION
[0042] The present invention relates to a method for recovering propylene-ethylene copolymer, comprising the following steps:
[0043] a) polymerizing propylene and ethylene in a continuous polymerization reactor under dynamic conditions in the presence of a single-site catalyst,
[0044] b) collecting the obtained propylene-ethylene copolymer powder from step a) to obtain a mixture (M) of propylene-ethylene copolymer powders having an MFR2 (ISO 1133, 230°C, 2.16 kg) in the range of 1.5 to 80.0 g / 10 min and an ethylene content in the range of 1.0 to 4.0 wt.-%, based on the total weight of the mixture (M),
[0045] c) mixing the mixture (M) and a clarifying agent in an extruder in the presence of a free radical initiator, wherein the amount of the clarifying agent is 0.01 to 0.5 based on the total weight of the propylene-ethylene copolymer powder mixture.
[0046] 1.0 wt%, and
[0047] d) Extruding the above mixture (M) into granules.
[0048] Step a)
[0049] The change from producing one grade of polymer to producing another grade of polymer generally requires a transition period in which the polymerization reactor switches to a new set of resin specifications and corresponding process conditions (such as reaction temperature, reactants and reactant concentration ratios). During the transition period from an initial polymerization reaction intended to produce an initial resin product meeting a first set of specifications to a target polymerization reaction intended to produce a target resin product meeting a second set of specifications, "inferior" polymers may be produced whose isotacticity or xylene soluble content (or other properties, such as melt flow rate and / or comonomer content) do not meet the first or second set of specifications. The transition from the above-mentioned first set of specifications to the second set of specifications is referred to herein as "dynamic conditions."
[0050] According to the present invention, the expression "dynamic conditions" relates to polymerization conditions, wherein the characteristics of the copolymer, such as the comonomer content, preferably the ethylene content, and / or the melt flow rate (MFR2) of the resulting copolymer, are gradually changed from a first predetermined ethylene content E1 to a second predetermined ethylene content E2, and / or from a first predetermined melt flow rate MFR 2-1 Gradually change to a second predetermined melt flow rate MFR 2-2 .
[0051] MFR 2-1 and MFR 2-2 Independently in the range of 1.5 to 80.0 g / 10 min (ISO 1133, 230° C., 2.16 kg), preferably in the range of 1.6 to 60 g / 10 min, more preferably 1.6 to 40 g / 10 min, and even more preferably 1.6 to 20 g / 10 min.
[0052] Based on the total weight of the respective polymers, E1 and E2 are each independently in the range of 1.0 to 4.0 wt%, preferably 1.2 to 3.8 wt%, more preferably 1.4 to 3.5 wt%, even more preferably in the range of 1.4 to 3.3 wt%.
[0053] The described gradual change of characteristic can comprise at least one increase or decrease in polymer characteristic.In addition, according to specific process conditions, it is possible that one (value of a) characteristic of polymer increases or decreases while another (value of a) characteristic of polymer decreases, increases or remains constant.
[0054] In addition, the gradual change of polymer characteristics can be achieved by adjusting one or more process parameters in the continuous polymerization reaction. Suitable, adjustable process parameters include ethylene feed rate, propylene feed rate, hydrogen feed rate, pressure, temperature, etc.
[0055] Preferably, the polymerization of propylene and ethylene under dynamic conditions in a continuous polymerization reactor is carried out in the presence of a single site catalyst, more preferably in the presence of a metallocene catalyst.
[0056] Specific examples of suitable single site and / or metallocene catalysts are disclosed in WO 2019 / 197384.
[0057] According to one embodiment of the present invention, the continuous polymerization reactor may include one or more of a slurry reactor, a gas phase reactor, or a combination thereof. A preferred slurry reactor is a loop reactor. In addition, the polymerization is preferably carried out in a sequential continuous polymerization reactor configuration, the reactor comprising an optional prepolymerization reactor configured in series, one or more slurry reactors, preferably one or more loop reactors, and one or more gas phase reactors.
[0058] Even more preferably, the polymerisation is carried out in a multistage process, such as the loop-gas phase process developed by Borealis A / S of Denmark, known as BORSTAR(R) technology, which is described, for example, in the patent literature, for example in EP-A-0887379 or WO 92 / 12182.
[0059] Step b)
[0060] Step b) comprises collecting the propylene-ethylene copolymer powder obtained in step a) to obtain a mixture (M) of propylene-ethylene copolymer powders having an MFR2 (ISO 1133, 230°C, 2.16 kg) in the range of 1.5 to 80.0 g / 10 min, preferably in the range of 1.6 to 60 g / 10 min, more preferably in the range of 1.6 to 40 g / 10 min and even more preferably in the range of 1.6 to 20 g / 10 min, and an ethylene content in the range of 1.0 to 4.0 wt-%, preferably in the range of 1.2 to 3.8 wt-%, more preferably in the range of 1.4 to 3.5 wt-%, even more preferably in the range of 1.4 to 3.3 wt-%, based on the total weight of the mixture (M).
[0061] According to one embodiment of the present invention, when the polymer produced in step a) has a first ethylene content E1 and a melt flow rate MFR 2-1 When the copolymer powder in step b) is collected, the polymer produced in step a) has a second ethylene content E2 and a melt flow rate MFR 2-2 When the amount of the copolymer powder in step b) is less than 0.05, the collection of the copolymer powder in step b) is stopped.
[0062] In other words, the collection of the copolymer powder begins before or while adjusting at least one process parameter.
[0063] To determine the end point of the collection step, i.e. the moment to stop collecting polymer powder, monitoring polymer characteristics may be useful. In some embodiments, the collection of polymer powder is stopped when process parameters in the continuous polymerization process remain constant again and / or when the reaction reaches a steady state.
[0064] Step c)
[0065] Step c) comprises mixing the mixture (M) and a clarifying agent in an extruder in the presence of a free radical initiator, wherein the amount of the clarifying agent is 0.01 to 1.0 wt % based on the total weight of the propylene-ethylene copolymer powder mixture.
[0066] Preferably, the propylene-ethylene copolymer powder (mixture (M)) collected in step b) is compounded in an extruder in the presence of a free radical initiator at normal process temperature, i.e. at a temperature between 190°C and 280°C. The initiator triggers the degradation of the propylene-ethylene copolymer; sometimes this process is also called "visbreaking". The visbreaking of the propylene-ethylene copolymer comprises several steps. The most relevant step is the decomposition of the initiator at high temperature, thereby forming free radicals. The free radicals can abstract hydrogen atoms from the polymer chains (H abstraction). Importantly, the tertiary free radicals of the polypropylene obtained in this way are unstable and undergo β-scission reactions, which cut the chains and reduce the molecular weight (or viscosity) of the polypropylene. As a result of the β-scission reaction, unsaturation (carbon-carbon double bonds) form end groups of new polymer molecules. This type of structure can be detected by different methods, for example 1 HNMR. 1 The chemical shifts at 4.72 and 4.78 ppm observed in H NMR can be attributed to the vinylidene terminated polypropylene and / or propylene-ethylene copolymer chains, which are caused by β-scission of tertiary polypropylene and / or propylene-ethylene copolymer macroradicals. During the visbreaking process, side reactions may occur. One of the main side reactions of tertiary polypropylene and / or propylene-ethylene copolymer macroradicals is the disproportionate termination of the macroradicals, resulting in the formation of internal vinylidene bonds. This can be explained by 1 H NMR is detected by chemical shift at 4.85 ppm. The total content of two types of vinylidene bonds indicates the content of macroradicals of polypropylene and / or propylene-ethylene copolymer, while the content of terminal C=C bonds indicates the degree of β-scission reaction in the system (Haiping Xing et al., Polymer 55 (2014) 5435-5444).
[0067] Suitable free radical initiators known in the art may be selected from organic peroxides, organic peresters, organic hydroperoxides and / or hydroxylamine esters.
[0068] The free radical initiator (preferably peroxide) is added in an amount of 0.1 to 5.0 wt%, preferably 1.0 to 4.0 wt%, more preferably 2.0 to 3.5 wt%, based on the total weight of the propylene-ethylene copolymer powder mixture (M).
[0069] A preferred free radical initiator is a synergistic visbreaking composition according to WO 2016 / 096687 A1 comprising a peroxide (i) and a hydroxylamine ester (ii).
[0070] Peroxide (i)
[0071] Typical organic peroxides are selected from 2,5-dimethyl-2,5-bis(tert-butyl-peroxy)hexane (DHBP) (sold for example under the trade names Luperox 101 and Trigonox 101), 2,5-dimethyl-2,5-bis(tert-butyl-peroxy)hexyne-3 (DYBP) (sold for example under the trade names Luperox 130 and Trigonox 145), dicumyl peroxide (DCUP) (sold for example under the trade names Luperox DC and Perkadox BC), di-tert-butyl peroxide (DTBP) (sold for example under the trade names Trigonox B and Luperox Di), tert-butylcumyl peroxide (BCUP) (sold for example under the trade names Trigonox T and Luperox 801) and bis(tert-butylperoxyisopropyl)benzene (DIPP) (sold for example under the trade names Perkadox 14S and Luperox DC).
[0072] Preferred peroxides are 5-dimethyl-2,5-bis(tert-butyl-peroxy)hexane (DHBP) and tert-butylcumyl peroxide (BCUP).
[0073] It is within the scope of the present invention to use one specific peroxide or a mixture of different peroxides.
[0074] The peroxide may be part of a masterbatch.
[0075] In the sense of the present invention, "masterbatch" is understood to mean a concentrated premix of propylene polymer and free radical former (peroxide).
[0076] The content of the peroxide compound in the peroxide masterbatch composition is preferably 1 to 50 wt%, such as 5 to 40 wt%, based on the total composition of the masterbatch.
[0077] Hydroxylamine ester (ii)
[0078] Suitable hydroxylamine esters are selected from hydroxylamine esters known in the art, such as those disclosed in WO 01 / 90113. A commercially available suitable hydroxylamine ester is sold, for example, by BASF
[0079] Synergistic viscosity reducing agent composition
[0080] A synergistic viscosity reducing agent composition as described in WO2016 / 096687A1 may preferably be used. A preferred synergistic viscosity reducing agent comprises the following amounts of peroxide (i) and hydroxylamine ester (ii): 1 wt% (i): 99 wt% (ii) to 99 wt% (i): 1 wt% (ii), preferably 20 wt% (i): 80 wt% (ii) to 95 wt% (i): 5 wt% (ii), more preferably 25 wt% (i): 75 wt% (ii) to 90 wt% (i): 10 wt% (ii), even more preferably 30 wt% (i): 70 wt% (ii) to 85 wt% (i): 15 wt% (ii), most preferably 50 wt% (i): 50 wt% (ii) to 85 wt% (i): 15 wt% (ii).
[0081] The weight percentages relate to the pure compounds (i) and (ii).
[0082] The peroxide and the hydroxylamine ester can be used directly as a mixture, or the two components of the composition can be added separately to the polypropylene and / or the propylene-ethylene copolymer.
[0083] Preferably, the peroxide and hydroxylamine ester are added directly to the polymer as a mixture.
[0084] Preferably, the hydroxylamine ester is added in the form of a masterbatch and the peroxide is added in pure form.
[0085] More preferably, the peroxide and the hydroxylamine ester are added in the form of a masterbatch.
[0086] Suitable clarifiers are known in the art. Exemplary clarifiers suitable for use in the present invention are disclosed in EP 1989 252 B1. Preferably, the clarifier is soluble in the polymer melt of the propylene-ethylene copolymer powder (M).
[0087] More preferably, the clarifying agent comprises a substituted or unsubstituted dibenzylidene sorbitol compound and / or a substituted or unsubstituted 1,2,3-trideoxy-4,6:5,7-bis-O-[(4-propylphenyl)methylene]-nonanol (nornitol) compound.
[0088] The amount of the clarifier is in the range of 0.05 to 1.0 wt%, preferably 0.1 to 0.8 wt%, more preferably 0.15 to 0.4 wt%, based on the total weight of the propylene-ethylene copolymer powder mixture.
[0089] Clarifying agents used herein can act as nucleating agents and thereby alter the crystallinity of the polymer.
[0090] Optionally, the mixing step c) can be carried out in the presence of further additives. Suitable further additives can be selected from antioxidants, antistatic agents and optical brighteners.
[0091] The optional antioxidant and / or antistatic agent may be present in a total amount of 0.05 to 1.0 wt. %, based on the total weight of the copolymer powder mixture.
[0092] The optional optical brightener may be present in an amount of 10 to 1000 ppm based on the total weight of the copolymer powder mixture.
[0093] Suitable optical brighteners are known in the art. For example, EP1989252B1 discloses a range of optical brighteners suitable for the present invention.
[0094] Preferably, an optical brightener is present which comprises a water-insoluble pigment.
[0095] Step d)
[0096] Step d) comprises extruding the mixture (M) into granules, wherein the granules have the following properties:
[0097] i) MFR2 (ISO 1133, 230°C, 2.16 kg) is 20 to 120 g / 10 min, preferably 40 to 115
[0098] g / 10min, more preferably 50 to 110 g / 10min, even more preferably 60 to 100 g / 10min.
[0099] within the enclosure;
[0100] ii) MFR 2颗粒 / MFR 2粉末 The ratio is >1;
[0101] iii) an ethylene content of 1.0 to 4.0 wt%, preferably 1.2 to 3.8 wt%, more preferably 1.4 to
[0102] 3.5 wt %, even more preferably in the range of 1.4 to 3.3 wt %,
[0103] iv) a crystallization temperature Tc determined by DSC according to ISO 11357-3:1999 in the range of 100 to 125°C, and
[0104] v) a flexural modulus of 850 MPa or more, the flexural modulus being 1000 MPa or more according to ISO 178.
[0105] The test was performed in three-point bending on injection molded samples of 80×10×4 mm prepared by 1873-2.
[0106] According to a preferred embodiment of the present invention, the particles also have at least one of the following properties:
[0107] - a melting temperature Tm determined by DSC according to ISO 11357-3:1999 in the range of 125 to 150°C; and / or
[0108] The gamma phase content is at least 70%, preferably 70 to 99%.
[0109] The expression "gamma phase content" used in this article is related to the 3 The orthorhombic gamma crystalline phase 100*Kγ correlation was determined by wide angle X-ray scattering (WAXS) on the injection molded plaque sample.
[0110] According to another aspect, the present invention also relates to propylene-ethylene copolymer particles obtainable by the above process.
[0111] Preferably, the propylene-ethylene copolymer particles have the following properties:
[0112] i) MFR2 (ISO 1133, 230°C, 2.16 kg) is 20 to 120 g / 10 min, preferably 40 to 115
[0113] g / 10min, more preferably 50 to 110 g / 10min, even more preferably 60 to 100 g / 10min.
[0114] within the enclosure;
[0115] ii) MFR 2颗粒 / MFR 2粉末 The ratio is >1;
[0116] iii) an ethylene content of 1.0 to 4.0 wt%, preferably 1.2 to 3.8 wt%, more preferably 1.4 to
[0117] 3.5 wt %, even more preferably in the range of 1.4 to 3.3 wt %,
[0118] iv) a crystallization temperature Tc determined by DSC according to ISO 11357-3:1999 in the range of 100 to 125°C, and
[0119] v) a flexural modulus of 850 MPa or more, the flexural modulus being 1000 MPa or more according to ISO 178.
[0120] The test was performed in three-point bending on injection molded samples of 80×10×4 mm prepared by 1873-2.
[0121] More preferably, the propylene-ethylene copolymer particles further have at least one of a melting temperature Tm of 130 to 150°C, measured by DSC according to ISO 11357-3:1999, and a gamma phase content of 70 to 99%, measured by wide angle X-ray scattering (WAXS).
[0122] By using the propylene-ethylene copolymer particles as described above for injection molding applications, an article, preferably a cup, comprising or consisting of the propylene-ethylene copolymer particles can be obtained.
[0123] Experimental Section
[0124] A) Measurement method
[0125] Melt flow rate
[0126] The melt flow rate (MFR) is measured according to ISO 1133 and is expressed in g / 10 min. The MFR indicates the fluidity and therefore the processability of a polymer. The higher the melt flow rate, the lower the viscosity of the polymer. The MFR of polypropylene is measured at a temperature of 230°C and a load of 2.16 kg.
[0127] Xylene Cold Solubility (XCS)
[0128] According to ISO 16152, 5th edition; 2005-07-01 at 25 ° C, the xylene cold soluble fraction (XCS, weight %) at room temperature was determined;.
[0129] Flexural modulus
[0130] Injection molded according to EN ISO 1873-2 80×10×4mm 3 The flexural modulus was determined by a 3-point bending test at 23°C according to ISO 178 on a test bar.
[0131] Charpy Notched Impact Strength (NIS)
[0132] The Charpy notched impact strength (NIS) was determined according to ISO 179 1eA at +23°C using 80 x 10 x 4 mm3 injection molded bar specimens prepared according to EN ISO 1873-2.
[0133] Haze
[0134] According to ASTM D1003-00, in 60×60×2 mm according to EN ISO 1873-2 3 Haze measurements were performed on injection molded plaques. Injection molded plaques were produced at a melt temperature of 230° C. Unless otherwise stated, the haze values presented herein were measured on 2 mm thick plaques.
[0135] Opto-Mechanical Ability (OMA)
[0136] The photomechanical ability (OMA) is the product of the flexural modulus and the Charpy notched impact strength, divided by the haze value (Haze2) on a 2 mm thick injection molded plaque:
[0137] OMA = (flexural modulus [MPa] * NIS [kJ / m2]) / haze 2 [%].
[0138] Determination of comonomers by NMR spectroscopy
[0139] Quantitative nuclear magnetic resonance (NMR) spectroscopy was further used to quantify the comonomer content and comonomer sequence distribution of the polymers. 1 H and 13 C was operated at 400.15 and 100.62 MHz, respectively, and quantitatively recorded in solution 13 C{ 1 H}NMR spectroscopy. 13 All spectra were recorded at 125°C with a C optimized 10 mm extended temperature probe head using nitrogen for all pneumatics. Approximately 200 mg of material was dissolved in 3 ml of 1,2-tetrachloroethane d2 (TCE-d2) along with chromium (III) acetylacetonate (Cr(acac)3) to give a 65 mM solution of the relaxant in the solvent (Singh, G., et al., Polymer Testing 28 5 (2009), 475). To ensure a homogeneous solution, the NMR tube was further heated in a rotating oven for at least 1 hour after initial sample preparation in a heating block. After insertion into the magnet, the tube was rotated at 10 Hz. This setup was chosen primarily for high resolution and accurate quantification of ethylene content. Standard single pulse excitation without NOE was used, with optimized tip angle, 1 second recycle delay and dual-level WALTZ16 decoupling scheme (Zhou, Z., et al., J. Mag. Reson. 187 (2007) 225; Busico, V., et al., Macromol. Rapid Commun. 2007, 28, 1128). A total of 6144 (6k) transients were acquired for each spectrum.
[0140] Using a dedicated computer program 13 C{ 1The H} NMR quantitative spectra are processed, integrated, and the relevant quantitative properties are determined based on the integration. All chemical shifts are indirectly referenced to the central methylene of the ethylene block (EEE) at 30.00 ppm using the chemical shift of the solvent. This method allows for comparable references even if this structural unit is not present. Characteristic signals corresponding to ethylene incorporation are observed (Cheng, HN, Macromolecules 17 (1984), 1950).
[0141] Characteristic signals corresponding to 2,1 red regional defects were observed (as described in L. Resconi, L. et al., Chem. Rev. 2000, 100 (4), 1253, Cheng, HN, Macromolecules 1984, 17, 1950 and WJ. Wang and S. Zhu, Macromolecules 2000, 33 1157), which require correction for the effect of regional defects on the measured properties. Characteristic signals corresponding to other types of regional defects were not observed.
[0142] Using the method of Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157), by 13 C{ 1 The comonomer fraction was quantified by integrating multiple signals across the spectral region in the {H} spectrum. This method was chosen for its robustness and ability to account for the presence of regional defects when required. The integration region was slightly adjusted to increase applicability over the entire range of comonomer content encountered. For systems where only isolated ethylene in the PPEPP sequence was observed, the method of Wang et al. was modified to reduce the impact of non-zero integrals at sites known to be absent. This method reduces the overestimation of ethylene content for such systems and is achieved by reducing the number of sites used to determine the absolute ethylene content to:
[0143] E=0.5(Sββ+Sβγ+Sβδ+0.5(Sδβ+Sαγ))
[0144] Using this set of sites, the corresponding integral equation becomes:
[0145] E=0.5(l H +l G +0.5(I C +I D ))
[0146] The same symbols used in the article by Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157) are used. The equations for the absolute propylene content are not modified.
[0147] The mole percentage of comonomer incorporation is calculated based on the mole fraction:
[0148] E[mol%]=100*fE
[0149] The weight percent of comonomer incorporation is calculated based on the mole fraction:
[0150] E[wt%]=100*(fE*28.06) / ((fE*28.06)+((1-fE)*42.08))
[0151] Differential Scanning Calorimetry (DSC)
[0152] Differential scanning calorimetry (DSC) analysis, melting temperature (Tm) and melting enthalpy (Hm), crystallization temperature (Tm) and enthalpy of melting (Hm) were measured on 5 to 7 mg samples using a TA Instrument Q200 DSC. C ) and heat of crystallization (Hc, H CR ). The DSC was run according to ISO 11357 / Part 3 / Method C2 with a hot / cold / hot cycle, a scan rate of 10°C / min, and a temperature range of -30 to +225°C.
[0153] Crystallization temperature (T C ) and heat of crystallization (H C ) is determined by the cooling step, while the melting temperature (Tm) and melting enthalpy (Hm) are determined by the second heating step.
[0154] Throughout this patent, the term T C or (T CR ) is understood to be the crystallization peak temperature determined by DSC at a cooling rate of 10 K / min (ie 0.16 K / sec).
[0155] Cup Test
[0156] Preparation of 840ml cup
[0157] Cups were produced from the polymer defined below by injection molding using an Engel speed 180 machine (supplied by Engel Austria GmbH) with a 35 mm stop screw. The melt temperature was adjusted to 245° C., the mold temperature to 10° C.; the injection speed was 770 cm 3 / s, injection time of 0.08s, followed by a holding pressure time of 0.1s, 1300 bar (down to 800 bar), cooling time of 1.5s, and a standard cycle time of 3.8s. The dimensions of the cup are as follows: height 100mm, top diameter 115mm, bottom diameter 95mm, bottom wall thickness 0.44mm, side wall thickness 0.40mm. The top load test is carried out according to an internal procedure generally consistent with ASTM D642 by compression between two plates connected to a universal testing machine at a test speed of 10mm / min. For the test, the cup is placed inverted (i.e., with the bottom facing the moving plate) in the test device and compressed to the collapse point, which is marked by the force drop on the force-deformation curve, where the maximum force is recorded. At least 8 cups are tested to determine the average result.
[0158] The drop test is performed on injection moulded cups. The cups are filled with water and covered with lids. During the pre-test, the estimated drop height is determined on 10 cups. The final test will be performed on 20 cups, starting from the predetermined drop height. In each run, 2 cups will be dropped. Depending on 2 breaks or 1 break / 1 no break (= neutral) or 2 no breaks, the next drop height is selected as lower / equal / higher for the next test run. A "break" in the sense of this test occurs when the cup shows at least one (visible) crack. If 2 breaks occur, the next drop height is selected as lower; if the result is neutral, the test is repeated at the same drop height; in case of a positive result (2 no breaks), the next drop height is selected as higher. The increase or decrease in height is 0.25 m, except for 0.1 m when the drop height is < 1.5 m. Depending on the drop height of the container after the first trend change or after the first "neutral" result, the final drop height is determined according to the following formula:
[0159] h e =Σ(ni.hi) / ng
[0160] where h e = Drop height
[0161] h i = Drop height
[0162] n i = the number of containers dropped from the corresponding height, and
[0163] n g =Total number of dropped containers.
[0164] Wide-angle X-ray scattering (WAXS)
[0165] Samples for WAXS measurements were prepared by adding 5 to 7 mg of sample to the DSC pan, heating it to 225 °C, waiting 5 min to eliminate the thermal history, and then cooling to 23 °C at a rate of 10 °C / min.
[0166] The crystallinity and polymorph composition were determined in reflection geometry using a Bruker D8 Discover with a GADDS x-ray diffractometer, which was operated under the following settings: x-ray generator: 30 kV and 20 mA; θ1 = 6° & θ2 = 13°; sample detector distance: 20 cm; beam size (collimator): 500 μm; duration / scan: 300 seconds. Three measurements were performed for each sample. The intensity vs. 2θ curve between 2θ = 10° and 2θ = 32.5° was obtained by integrating the two-dimensional spectrum.
[0167] Then, quantification of the intensity vs. 2θ curve was performed as follows:
[0168] On amorphous iPP samples prepared by solvent extraction, intensity vs. 2θ curves were obtained using the same measurement setup. The amorphous halo was obtained by smoothing the intensity vs. 2θ curves. The amorphous halo was subtracted from each intensity vs. 2θ curve obtained on the actual sample, which formed the crystalline curve.
[0169] The crystallinity index X is defined by the crystallization curve and the area under the original curve using the method proposed by Challa et al. (Makromol. Chem. vol. 56 (1962), pages 169-178). C ,as follows:
[0170] X C =[(area under the crystallization curve) / (area under the original spectrum)]x100.
[0171] In a two-phase crystalline system (containing α- and β-modifications), the amount of β-modification in crystalline phase B was calculated using the method proposed by Turner Jones et al. (Makromol. Chem. Vol. 75 (1964), pages 134-158) as follows:
[0172] B=[Iβ(300)] / [Iα(110)+Iα(040)+Iα(130)+Iβ(300)],
[0173] In the formula, I β (300) is the intensity of the B(300) peak, I α (110) is the intensity of the α(110) peak, I α (040) is the intensity of the α(040) peak, and I α(130) is the intensity of the α(130) peak obtained after subtracting the amorphous halo.
[0174] In a two-phase crystalline system (containing α- and γ-modifications), the amount of γ-modification in the crystalline phase G (i.e., Kγ) is calculated using the method developed by Pae (J. Polym. Sci., Part A2, vol. 6 (1968), pages 657-663) as follows:
[0175] G=[Iγ(117)] / [Iα(130)+Iγ(117)],
[0176] Among them, I α (130) is the intensity of the α(130) peak, I γ (117) is the γ(117) peak intensity obtained after subtracting the baseline junction of the bases of these peaks.
[0177] B) Materials
[0178] Preparation of single-site catalyst systems
[0179] Catalyst complex
[0180] The following metallocene complex was used as described in WO 2019 / 179959:
[0181] Preparation of MAO-silica carrier
[0182] A steel reactor equipped with a mechanical stirrer and a filter screen was flushed with nitrogen 10, and the reactor temperature was set to 20°C. Next, a silica grade DM-L-303 (5.0 kg) pre-calcined at 600°C from AGC Si-Tech was added by a feed drum, and then carefully pressurized and decompressed with nitrogen using a manual valve. Toluene (22 kg) was then added. The mixture was stirred for 15 minutes. A solution of 30% by weight MAO in toluene (9.0 kg) from Lanxess was then added through the feed line at the top of the reactor within 70 minutes. The reaction mixture was then heated to 90°C and stirred for another two hours at 90°C. The slurry was precipitated and the mother liquor was filtered out. The catalyst was washed twice with toluene (22 kg) at 90°C, followed by sedimentation and filtration. The reactor was cooled to 60°C, and the solid was washed with heptane (22.2 kg). Finally, the SiO2 treated with MAO was dried for 2 hours under a 60° nitrogen stream, and then stirred and dried for 5 hours under vacuum (-0.5 barg). The MAO treated support was collected as a free flowing white powder and found to contain 12.2 wt% Al.
[0183] Preparation of single-site catalyst systems
[0184] At 20°C, 30 wt% MAO in toluene (0.7 kg) was added to a steel nitrogen-filled reactor via a burette. Toluene (5.4 kg) was then added under stirring. The above metallocene complex (93 g) was added from a metal cylinder and then rinsed with 1 kg of toluene. The mixture was stirred for 60 minutes at 20°C. Triphenylmethyl tetrakis(pentafluorophenyl)borate (91 g) was then added from a metal cylinder and then rinsed with 1 kg of toluene. The mixture was stirred at room temperature for 1 hour. The resulting solution was added to the stirred filter cake of the MAO-silica support prepared as described above within 1 hour. The filter cake was left for 12 hours and then dried under a stream of N2 at 60°C for 2 hours and then stirred and dried under vacuum (-0.5 barg) for 5 hours.
[0185] Preparation of the base polymer of the present invention
[0186] Both base polymers of the invention were produced in the presence of a single-site catalyst prepared as described above in a Borstar pilot plant comprising a reactor train consisting of a prepolymerization reactor, a loop reactor and a (first) gas phase reactor (GPR1). During production, the conditions in the prepolymerization reactor were kept constant. Temperature 20°C, residence time 20 min. The concentration of H2 (expressed as H2 / C3 for both loop and GPR1), the concentration of C2 (expressed as C2 / C3) were varied during the collection period.
[0187] The production conditions of the base polymer 1 (IB1) of the present invention are given in the figure: Figure 1a H2 / C3 in the ring tube, Figure 1b C2 / C3 in the ring tube, Figure 1c GPR1 H2 / C3 and Figure 1d C2 / C3 in GPR1 and Figure 1e The loop side split was collected as a mixture of propylene-ethylene copolymers (IB1), and due to the dynamic process conditions, the comonomer content, molecular weight and melt flow rate of the individual polymers were different. The MFR2 of this mixture IB1 was 6.8 g / 10 min and the ethylene content was 1.8 wt%. At the beginning of the collection, the C2 after GPR1 was 1.6 wt% and the MFR was 9.1 g / 10 min. At the end of the collection, the C2 after GPR1 was 3.2 wt% and the MFR was 1.4 g / 10 min.
[0188] The production conditions of the base polymer 2 (IB2) of the present invention are given in the figure: Figure 2a H2 / C3 in the ring tube, Figure 2b C2 / C3 in the ring tube, Figure 2c GPR1 H2 / C3 and Figure 2d C2 / C3 in GPR1 and Figure 2eThe loop side stream is also collected as a mixture of propylene-ethylene copolymers, and due to the dynamic process conditions, the comonomer content, molecular weight and melt flow rate of the individual polymers are different. The MFR2 of this mixture IB2 is 2.4 g / 10 min and the ethylene content is 3.0 wt%. At the beginning of the collection, the C2 after GPR1 is 3.3 wt% and the MFR is 2.5 g / 10 min. At the end of the collection, the C2 after GPR1 is 2.6 wt% and the MFR is 2.4 g / 10 min.
[0189] The comparative base polymer (CB) was produced in the presence of a non-phthalate based Ziegler-Natta catalyst. The process is shown in Table 1. Details about the catalyst used are disclosed, for example, in the earlier application EP2999721.
[0190] Table 1: Polymerization process of CB base polymer
[0191]
[0192] The granulation of PP powder and additives was carried out in a twin-screw extruder with a screw diameter of 18 mm, a melt temperature of 240 °C and an output of 7 kg / h. The following additives were used:
[0193] Irganox B 215—is an antioxidant commercially available from BASF;
[0194] Ceasit AV FI Veg - provided by Baerlocher;
[0195] 426-produced by Danisco (DuPont Group);
[0196] DHBP-5-IC5 - provided by United Initiators;
[0197] Milliad 3988 and Milliad NX8000ECO - provided by Milliken Chemical;
[0198] Bright 100 - manufactured by MPI-CHEMI BV.
[0199] All chemicals were used as received.
[0200] Table 2: Granulation additives and product properties
[0201]
[0202] It can be seen that the inventive examples show better optical properties, as indicated by lower haze values and improved OMA. In addition, the inventive examples exhibit good mechanical properties, as reflected by higher OMA and improved results in the cup test.
[0203] Specifically, in the cup application test, the cup formation process was good, and the cycle time was similar to that of the comparative example (CE1). IE1 and IE2 had an improved high stiffness (top load) / high impact (drop height) combination compared to CE1. IE3 had a lower maximum force, but the drop height was the highest among all the examples.
Claims
1. A method for recovering propylene-ethylene copolymer, comprising the following steps: a) polymerizing propylene and ethylene in a continuous polymerization reactor under dynamic conditions in the presence of a single-site catalyst, b) collecting the propylene-ethylene copolymer obtained in step a), which comprises at least two fractions of propylene-ethylene copolymer powder (P1, P2) to obtain a propylene-ethylene copolymer mixture (M), said mixture (M) having an MFR2 in the range of 1.5 to 80.0 g / 10 min, an ethylene content in the range of 1.0 to 4.0 wt.-%, based on the total weight of said mixture (M), wherein said MFR2 is measured according to ISO 1133 at a temperature of 230° C. and a load of 2.16 kg, c) mixing the mixture (M) and a clarifying agent in an extruder in the presence of a free radical initiator, The amount of the clarifying agent is 0.01 to 1.0 wt % based on the total weight of the propylene-ethylene copolymer powder mixture, and d) extruding the mixture into granules; Wherein, in step a), the dynamic conditions are such that the ethylene content and melt flow rate (MFR2) of the obtained copolymer gradually change from a first predetermined ethylene content E1 to a second predetermined ethylene content E2, and / or from a first predetermined melt flow rate MFR 2-1 Gradually change to a second predetermined melt flow rate MFR 2-2 ; Wherein, when the polymer produced in step a) has a first predetermined ethylene content E1 and a first predetermined melt flow rate MFR 2-1 When the copolymer powder in step b) is collected, and when the polymer produced in step a) has a second predetermined ethylene content E2 and a second predetermined melt flow rate MFR 2-2 When the copolymer powder in step b) is collected, Among them, MFR 2-1 and MFR 2-2 independently in the range of 1.5 to 80.0 g / 10 min; E1 and E2 independently in the range of 1.0 to 4.0 wt %, wherein the MFR 2-1 and MFR 2-2 Determined according to ISO 1133 at a temperature of 230°C and a load of 2.16 kg; and wherein the propylene-ethylene copolymer particles obtained in step d) have the following properties: i) MFR2 is in the range of 20 to 120 g / 10 min, wherein the MFR2 is determined according to ISO 1133 at a temperature of 230° C. and a load of 2.16 kg, ii) MFR 2颗粒 / MFR 2粉末 The ratio is >1, iii) an ethylene content in the range of 1.0 to 4.0 wt. %, iv) a crystallization temperature Tc determined by DSC according to ISO 11357-3:1999 in the range of 100 to 125°C, and v) a flexural modulus of 850 MPa or more, the flexural modulus being determined in 3-point bending in accordance with ISO 178 on injection-molded specimens of 80×10×4 mm prepared in accordance with EN ISO 1873-2.
2. The method according to claim 1, wherein: The free radical initiator is an organic peroxide.
3. The method according to claim 1 or 2, wherein: The clarifier is soluble in the polymer melt.
4. The method according to claim 1 or 2, wherein: The clarifying agent includes a substituted or unsubstituted dibenzylidene sorbitol compound.
5. The method according to claim 1 or 2, wherein: The mixing step c) is carried out in the presence of further additives selected from antioxidants and antistatic agents and optical brighteners, the total amount of which is 0.05 to 1.0 wt. % based on the total weight of the copolymer powder mixture, and the amount of the optical brightener is 10 to 1000 ppm.
6. The method according to claim 5, wherein: The optical brighteners include water-insoluble pigments.
7. The method according to claim 1 or 2, wherein: The extruded particles have a melting temperature Tm of 130 to 150° C., determined by DSC according to ISO 11357-3:1999, and / or a gamma phase content of at least 70%, determined by wide angle X-ray scattering as described herein.
8. Propylene-ethylene copolymer particles obtainable by the process according to any one of claims 1 to 7.
9. The propylene-ethylene copolymer particles according to claim 8, having the following properties: i) MFR2 is in the range of 20 to 120 g / 10min, wherein, The MFR2 is measured according to ISO 1133 at a temperature of 230°C and a load of 2.16 kg, ii) MFR 2颗粒 / MFR 2粉末 The ratio is >1, iii) an ethylene content in the range of 1.0 to 4.0 wt. %, iv) a crystallization temperature Tc determined by DSC according to ISO 11357-3:1999 in the range of 100 to 125°C, and v) a flexural modulus of 850 MPa or more, the flexural modulus being determined in 3-point bending in accordance with ISO 178 on injection-molded specimens of 80×10×4 mm prepared in accordance with EN ISO 1873-2.
10. The propylene-ethylene copolymer particles according to claim 8 or 9, having at least one of a melting temperature Tm of 130 to 150°C, determined by DSC according to ISO 11357-3:1999, and a gamma phase content of 70 to 99%, determined by wide angle X-ray scattering as described herein.
11. An article comprising the propylene-ethylene copolymer particles according to any one of claims 8 to 10.
12. The article according to claim 11, consisting of the propylene-ethylene copolymer particles according to any one of claims 8 to 10.
13. Use of the propylene-ethylene copolymer particles according to any one of claims 8 to 10 for injection molding applications.
14. A cup comprising the propylene-ethylene copolymer particles according to any one of claims 8 to 10.
15. The cup according to claim 14, consisting of the propylene-ethylene copolymer particles according to any one of claims 8 to 10.
Citation Information
Patent Citations
Process and apparatus for preparing propylene homopolymers and copolymers
EP0887379A1
Compositions and method for making clarified articles
EP1989252B1
Propylene copolymer for thin-wall packaging
EP2999721A1
Multi-stage process for producing polyethylene
WO1992012182A1
Hydroxylamine esters as polymerization initiators
WO2001090113A1